The Characteristics of Patients With Possible Transient Ischemic Attack and Minor Stroke in the Hunter and Manning Valley Regions, Australia (the INSIST Study) - Tomari, Shinya; Magin, Parker; Lasserson, Daniel; Quain, Debbie; Valderas, Jose M.; Dewey, Helen M.; Barber, P. Alan; Spratt, Neil J.; Cadilhac, Dominique A.; Feigin, Valery L.; Rothwell, Peter M.; Zareie, Hossein; et al. (Frontiers in Neurology, 2020)
Background: Transient ischemic attack (TIA) and minor stroke (TIAMS) are risk factors for stroke recurrence. Some TIAMS may be preventable by appropriate primary prevention. We aimed to recruit “possible-TIAMS” patients in the INternational comparison of Systems of care and patient outcomes In minor Stroke and TIA (INSIST) study. Methods: A prospective inception cohort study performed across 16 Hunter–Manning region, Australia, general practices in the catchment of one secondary-care acute neurovascular clinic. Possible-TIAMS patients were recruited from August 2012 to August 2016. We describe the baseline demographics, risk factors and pre-event medications of participating patients. Results: There were 613 participants (mean age; 69 ± 12 years, 335 women), and 604 (99%) were Caucasian. Hypertension was the most common risk factor (69%) followed by hyperlipidemia (52%), diabetes mellitus (17%), atrial fibrillation (AF) (17%), prior TIA (13%) or stroke (10%). Eighty-nine (36%) of the 249 participants taking antiplatelet therapy had no known history of cardiovascular morbidity. Of 102 participants with known AF, 91 (89%) had a CHA2DS2-VASc score ≥ 2 but only 47 (46%) were taking anticoagulation therapy. Among 304 participants taking an antiplatelet or anticoagulant agent, 30 (10%) had stopped taking these in the month prior to the index event. Conclusion: This study provides the first contemporary data on TIAMS or TIAMS-mimics in Australia. Community and health provider education is required to address the under-use of anticoagulation therapy in patients with known AF, possibly inappropriate use of antiplatelet therapy and possibly inappropriate discontinuation of antiplatelet or anticoagulation therapy.